Concentrations of rare earth elements in pore waters of IODP Holes 323-U1345A and 323-U1345B - Tseren-Ochir Soyol-Erdene; Youngsook Huh (PANGAEA, 2016)
We studied the diagenetic behavior of rare earth elements (REEs) in a highly productive passive margin setting of the Bering Sea Slope. Site U1345 was drilled during the Integrated Ocean Drilling Program Expedition 323 at a water depth of 1008 m currently in the center of an oxygen minimum zone. Pore water concentrations of fourteen REEs were determined down to ~ 140 meters below the seafloor (mbsf). The REE concentrations were higher in the pore water than the deep seawater, indicating that there was significant liberation from the sediments during diagenesis. There was a major peak at ~ 10 mbsf that was more pronounced for the heavy REE (HREE); this peak occurred below the sulfate-methane transition zone (6.3 mbsf) and coincided with high concentrations of dissolved iron and manganese. At ~ 2 mbsf, there was a minor peak in REE and Mn contents. Below ~ 40 mbsf, the REE concentration profiles remained constant. The Ce anomaly was insignificant and relatively constant (PAAS-normalized Ce/Ce = 1.1 ± 0.2) throughout the depth profile, showing that the Ce depleted in seawater was restored in the pore water. HREE-enrichment was observed over the entire 140 m except for the upper ~ 1 m, where a middle REE (MREE)-bulge was apparent. REE release in shallow depths (2-4 mbsf) is attributed to the release of light REEs (LREEs) and MREEs during the organoclastic reduction of Mn oxides in anoxic sediments. The high HREE concentrations observed at ~ 10 mbsf can be attributed to the reduction of Fe and Mn minerals tied to anaerobic oxidation of methane or, less significantly, to ferromagnesian silicate mineral weathering. The upward diffusion flux across the sediment-water interface was between 3 (for Tm) and 290 (for Ce) pmol/m**2/y.
Supplement to: Soyol-Erdene, T-O; Huh, Y (2013): Rare earth element cycling in the pore waters of the Bering Sea Slope (IODP Exp. 323). Chemical Geology, 358, 75-89, https://doi.org/10.1016/j.chemgeo.2013.08.047